2017
DOI: 10.1111/bjet.12572
|View full text |Cite
|
Sign up to set email alerts
|

Students' insights on the use of video lectures in online classes

Abstract: Video lectures (VL), considered an effective means for delivering course content and infusing teaching presence in the virtual environment, have become very popular in education. The purpose of this study was to investigate online student experiences with VL focusing on their opinion of usefulness of VL, their satisfaction with them and their perception of learning derived from them. Our findings show that students' satisfaction with VL has a strong relationship with positive overall learning experience and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
110
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(132 citation statements)
references
References 27 publications
14
110
1
7
Order By: Relevance
“…These shortcomings were addressed subsequently through buying advanced version of the software that allows more time, and better opportunity to interact with students.COVID pandemic made us realize the importance of online training for our pediatric postgraduate students. Students' satisfaction levels with online learning were comparable to the previous studies [3]. Apart from gain in knowledge, the present study revealed the impact of online learning on the morale of our students by creating a diversion from the ongoing pandemic situation.…”
supporting
confidence: 83%
“…These shortcomings were addressed subsequently through buying advanced version of the software that allows more time, and better opportunity to interact with students.COVID pandemic made us realize the importance of online training for our pediatric postgraduate students. Students' satisfaction levels with online learning were comparable to the previous studies [3]. Apart from gain in knowledge, the present study revealed the impact of online learning on the morale of our students by creating a diversion from the ongoing pandemic situation.…”
supporting
confidence: 83%
“…A very similar pattern of feedback was received for both interventions: that online lectures were most favored (supporting the findings of MacPherson & Nunes, 2004;Mitra et al, 2010;Borup et al, 2011;Carmichael et al, 2017;Crook & Schofield, 2017;Scagnoli et al, 2017) and that the podcasts were the most criticized (Lawlor and Donnelly, 2010). Views were mixed on the use of outdoor videos to assess urban trees in the second intervention, some students wanted higher production values in terms of technical content and sound recording.…”
supporting
confidence: 62%
“…There are several studies that found the use of audio/visual learning resources for online learners to be effective, especially the use of instructional video and online lectures (MacPherson & Nunes, 2004;Mitra et al, 2010;Borup et al, 2011;Carmichael et al, 2017;Crook & Schofield, 2017;Scagnoli et al, 2017). Although now a popular delivery format in online courses, moving away from a high level of reading content, Pomales-Garcia and Liu (2006) warn against providing overlong videos or lectures.…”
Section: Creating Effective Learning Resources For Online Coursesmentioning
confidence: 99%
“…E-learning has been an important aspect of the current undergraduate curriculum delivery wherein reports of shortage of medical teachers have been reported (9).The adoption of the same within the medical colleges is expected to promote self directed learning and lifelong learning .Thus it will bene t both the teachers as well as the students (10). Similar experience shared by Scagnoli et al shows the importance of online training in COVID pandemic pediatric undergraduate students (11). Flexibility of E learning which can provide information to the students beyond the speci ed timings of teaching in class and gives freedom to read and learn whenever they feel the need for the same was documented in Nigeria study.…”
Section: Discussionmentioning
confidence: 89%